CHARACTERIZATION AND EVALUATION OF CeO2-MgO MIXED OXIDE SUPPORTED Ni CATALYST FOR DRY REFORMING OF METHANE - ALI, BASEM MOHAMMED (2019)
Dry reforming of methane (DRM) is becoming an appealing research topic because of the urgent need to minimize global warming and the demand for alternative energy resources.